Longitudinal investigations of development in handball and its association with relative age effects - Schorer, Jörg; Faber, Irene; Büsch, Dirk; Baker, Joseph; Wattie, Nick (Frontiers in Sports and Active Living, 2025)
In this paper, we describe two studies on the association among long-term developmental outcomes and relative age effects. To extend or compliment the cross-sectional work done previously, these studies take different approaches to investigate the association of relative age effects on long-term development. In the first, a retrospective approach is taken, while in the second, developmental data for players over a 4-year period is considered. In study 1 the association between relative age effects and later performance at the adult level is presented. The results show different patterns for females and males. In the second study, development during the national youth development system in handball, over four points in time, are presented. Again, changes over time in birth quartile distribution can be seen. These studies suggest relative age researchers should embrace longitudinal designs. These types of approaches would allow explorations of the association of other variables with the observed relative age effects.